2011
DOI: 10.5352/jls.2011.21.9.1288
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects of Resveratrol via mTOR and COX-2 Signal Pathways in MCF-7 Breast Cancer Cells

Abstract: Resveratrol, a kind of phytochemical, is presented in grape skins. Resveratorl exerts antiproliferative, anti-cancer and pro-apoptotic activities in cancer cells. Mammalian target of rapamycin (mTOR) is a critical regulator of cellular growth and proliferation, and it is known to be a strategic target for anti-cancer therapeutic uses. mTOR is a major downstream of the PI3K/Akt pathway, which is activated in various cancer cells. It also plays an important role in the survival, proliferation and angiogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Also, this combination selectively inhibited COX-2 but not COX-1 (Lev-Ari, Strier et al, 2005;Lev-Ari, Zinger et al, 2005). S. H. Lee et al (2012) showed that curcumin inhibits COX-2 and its downstream genes including vasodilator-stimulated phosphoprotein, leading to apoptosis induction in MCF-7 cells. The authors showed that COX-2 suppression by curcumin was mediated through AMP-activated protein kinase (AMPK).…”
Section: Inhibition Of Cox-2mentioning
confidence: 99%
“…Also, this combination selectively inhibited COX-2 but not COX-1 (Lev-Ari, Strier et al, 2005;Lev-Ari, Zinger et al, 2005). S. H. Lee et al (2012) showed that curcumin inhibits COX-2 and its downstream genes including vasodilator-stimulated phosphoprotein, leading to apoptosis induction in MCF-7 cells. The authors showed that COX-2 suppression by curcumin was mediated through AMP-activated protein kinase (AMPK).…”
Section: Inhibition Of Cox-2mentioning
confidence: 99%
“…Regulation of mTORC1 by phosphorylation of TSC2 induces cell survival and growth [5]. Also, inhibition of the Akt/mTOR signaling pathway induces decrease in COX-2 expression [14,40]. Furthermore, the inactive form of GSK-3β cannot degrade βcatenin, and its presence leads to β-catenin translocation to the nucleus.…”
Section: Cme Treatment Regulates Expression Of Apoptosis-related Prot...mentioning
confidence: 99%
“…COX-2 expression is controlled by both the Akt/ mTOR and GSK-3β/β-catenin signaling pathways [10][11][12][13]. COX-2 inhibition leads to apoptosis through regulation of Bcell lymphoma 2 (Bcl-2) and pro-apoptotic proteins such as Bax and Bak, and induces G1 cell cycle arrest through decreasing cyclin D1 activity [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%